The Current Status of the Fermilab Muon g–2 Experiment - Nandita Raha (Universe, 2019)
The anomalous magnetic moment of the muon can be both measured and computed to a very high precision, making it a powerful probe to test the Standard Model and search for new physics. The previous measurement by the Brookhaven E821 experiment found a discrepancy from the SM predicted value of about three standard deviations. The Muon g–2 experiment at Fermilab will improve the precision to 140 parts per billion compared to 540 parts per billion of E821 by increasing statistics and using upgraded apparatus. The first run of data taking has been accomplished in Fermilab, where the same level of statistics as E821 has already been attained. This paper, summarizes the current experimental status and briefly describes the data quality of the first run. It compares the statistics of this run with E821 and discusses the future outlook.